Sanções políticas como violação à livre concorrência em matéria tributária - Águila, João Gabriel Casemiro (2022)
The political sanctions are legal institutes historically linked to unconstitutional administrative measures, with the jurisprudence of the Supreme Court exercising a decisive role in the conceptual conformation of the indirect mechanics of the tax debt enforcement, established by the Precedents 70, 323 and 547. Working as a sign of the legal system operational's enclosure the law legitimates the constitutional concepts mutation by using its own language, with the concept of political sanctions having undergone mutations characteristic of the jurisprudential evolution, making necessary to study its resignification towards the constitutional precepts put into consideration. For this purpose, we utilizze the normative methodology of the Logical- Semantic Constructivism, using the jurisprudence as a source of research, as such as the doctrine and contextualized legislation in order to understand this institute. Proposing to build a new semantical conception of the non-pecuniary sanctions that narrow economic freedom rights in constitutional disagreement, qualified as political sanctions, in order to emphasize the conformation of the Free Competition Principle applied by the Supreme Court as an excludent of material unconstitutionality. Therefore, is necessary to ponde typology constitutionally qualified to tax matters, distinguishing its cycle of positivation and applicability of its preventive legal regime, by establishing special criterias for taxation, and, in its repressive sense, as a norm of sanctioning nature. the principle according to the